Oikonomy: towards the impossible possibility of justice in the context of globalisation - Meylahn, J-A (Nederduitse Gereformeerde Teologiese Tydskrif, 2009)
This article explores the concept of oikos in the context of the oikonomy of globalisation. Oikos is understood within the norming and naming of ever-greater households, such as the city and the nation state within globalisation. In this norming and naming the impossible possibility of justice is discovered. Can God’s household (God’s oikos), God’s city, be understood as a household that is continuously challenged by the other who is marginal and/or excluded and who knocks on the door of the oikos seeking justice and hospitality? This understanding of God’s household, the city to come, would challenge our global cities to ever-greater hospitality, truer cosmopolitanism and continuous forgiveness.